Analysis of Low-Energy and Low-Glycemic Index Diets Published at the Internet Portals - Kozirok, W. (Scientific Journal of Gdynia Maritime University, 2018)
The internet portals for human nutrition and dietetics have become very popular recently. The aim of the study was to analyze and evaluate the nutritional value of low-energy and low-glycemic diets published on the Internet. The analyzed material consisted of 7 day menu planner. Assessment included the supply of energy and selected nutrients necessary for correct functioning of the human body. The study showed poor quality of those diets. Most diets were unbalanced in terms of supply of important nutrients for health and did not meet the requirements of standard nutrition. The low nutritional value of diets offered by the internet portals can result in serious health effects. There is a need to promote reliable knowledge and education in this area.